Analysing match attendance in the European Rugby Cup - Vincent Hogan; Patrick Massey; Shane Massey (University College Dublin, UCD School of Economics, 2014)
Using data from 1,226 matches played over 18 seasons, we analyse match attendances in the group stages of the European Rugby Cup (ERC). We find that short-run (match) uncertainty had little effect on attendances. This finding is significant as the ERC has been replaced by a new competition which may be more unbalanced due to differences in the distribution of revenue between the participating teams. Medium-term uncertainty, i.e. the possibility of the home team reaching the knock-out stages, had a significant impact on attendances. Measures designed to make matches more attractive, e.g. bonus points for high scoring, had little effect.
Keywords: D12; D21; L22; L23; L83; 330; professional team sports; competitive balance; consumer demand